Determination of Galendo’s Shelf Life on Various of Storage Temperatures by Arrhenius Method - Asep Dedy Sutrisno; Wisnu Cahyadi (GoAcademica Research & Publishing, 2021)
This study aims to estimate the shelf life by applying the Arrhenius formula model to